(untitled) (Journal of Universal Science Research, 2023)
Albinism is a group of hereditary pathologies characterized by a violation or complete absence of skin, hair, eye pigmentation. The main symptoms of the disease are very pale skin and hair, blue or red eyes, and in some cases, vision impairment. The diagnosis of albinism is made based on the current condition of the patient, as well as genetic tests. To date, there is no specific treatment for albinism, palliative therapy (correction of vision) is used, and there are a number of recommendations for patients to behave in the sun, protect the skin and reduce thelikelihood of complications.